A Test of Policy Makers' Formal and Lay Theories Regarding Health Care Prices. (January 2019) - Fitzgerald, M. Paula; Yencha, Christopher
Politicians, think tanks, and advocacy groups have proposed paths to reduce prices and improve outcomes in the U.S. health care market. These paths tend to follow a combination of formal neoclassical economic theory and lay theory that posits solutions focused on increasing competition, reducing regulations, and normative beliefs about price→quality and price→cost relationships. The authors identify these formal and informal theories and test five tenets of health care reform. The results, based on over seven million consumer–hospital interactions across the United States, when combined with other empirical work, suggest that increased competition among hospitals is associated with lower hospital procedure prices; however, increased competition among insurers is associated with higher prices. Policy makers should not, in the current environment, rely on the tenet that reducing regulations will reduce hospital prices, nor should they assume that health care quality and price are positively correlated. The authors discuss the complexity of the health care market and identify possible reasons why the market does not always operate as predicted. Finally, the authors offer policy implications and research directions.